The complete mitochondrial genome of Africa's largest freshwater copepod, Lovenula raynerae. Issue 1 (2nd January 2019) - Jooste, Candice M.; Emami-Khoyi, Arsalan; Gan, Han Ming; Wasserman, Ryan J.; Dalu, Tatenda; Teske, Peter R.
Abstract: Lovenula raynerae is the largest known African freshwater copepod. To date, it has only been sampled from ephemeral freshwater ecosystems. This paper reports the complete mitochondrial genome of L. raynerae, which was found to be 14, 365 bp long. A base composition of 33.5% base A, 19.3% base G, 34.6% base T, and 12.5% base C was found, with 13 protein-coding genes, 22 tRNAs, and 2 rRNAs. This paper contributes to an improved understanding of phylogenetic relationships in an important crustacean group.